2022
DOI: 10.7759/cureus.28334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Ischemia Modified Albumin in Patients With COVID-19 Pneumonia: A Case-Control Study

Abstract: Introduction: Various biomarkers are used when evaluating the hospitalization needs of patients diagnosed with Coronavirus disease (COVID-19). Ischemia-modified albumin (IMA) is a biomarker that causes blood levels to increase as a result of hypoxia and acidosis. We think that an increase in IMA in the blood may be caused by hypoxia stemming from lung damage. This study aimed to compare the mean/median of the blood IMA value in patients with pneumonia due to COVID-19 infection with a control group. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Altıntaş et al [19] could not find a statistically significant difference between the patients with COVID-19 pneumonia and the control group in terms of blood IMA levels. When blood IMA levels were compared according to the severity of pneumonia, any statistically significant difference could not be found between mild-moderate and severe pneumonia groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Altıntaş et al [19] could not find a statistically significant difference between the patients with COVID-19 pneumonia and the control group in terms of blood IMA levels. When blood IMA levels were compared according to the severity of pneumonia, any statistically significant difference could not be found between mild-moderate and severe pneumonia groups.…”
Section: Discussionmentioning
confidence: 85%
“…When blood IMA levels were compared according to the severity of pneumonia, any statistically significant difference could not be found between mild-moderate and severe pneumonia groups. However, patients with lung involvement were included in both groups, and it was reported that no differ-ence was found between mild-moderate and severe groups due to the classification difference between studies [19]. Yıldız et al [20] compared IMA levels of COVID-19 patients with and without lung involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In Yucel et al’s study with 70 patients in the ICU, the serum IMA levels were determined to be significantly higher compared to the healthy control group [ 27 ]. However, in the study of Altıntas et al, no significant difference was determined in the serum IMA levels between the COVID-19 and the control groups [ 28 ]. Many studies have shown that increasing IMA levels contribute to our knowledge about the biomarkers in the pathophysiology of COVID-19, enabling the detection and early diagnosis of pneumonic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Acar et al’s study shows that the levels of IMA can be utilized for risk stratification and estimation of mortality in severe COVID-19 pneumonia patients admitted to the emergency unit [ 26 ]. In the study of Altıntas et al, no significant difference was found between mild-moderate and severe pneumonia groups and serum IMA levels in COVID-19 patients [ 28 ]. In another study, the severity of pneumonia was separated into three groups as mild, moderate, and severe/critical in 95 patients hospitalized due to COVID-19 pneumonia, and although the degree of the disease and the level of IMA increased, statistical significance was not found [ 29 ].…”
Section: Discussionmentioning
confidence: 99%